2015
DOI: 10.1515/jbcr-2015-0148
|View full text |Cite
|
Sign up to set email alerts
|

Multivessel Disease As A Prognostic Factor For Mortality In STEMI Patients

Abstract: Summary The main objective of this analysis was to define the influence of multivessel disease involvement compared to single vessel disease on mortality rates in STEMI patients. The retrospective study included 549 patients, hospitalized with STEMI in St. Ekaterina University Hospital (age - 62.66±12.56; women - 31.3%) from 01.06.2008 to 30.06.2011. One-vessel disease was found in 232 patients (44%) as compared to two-vessel disease in 165 patients - 31% and multivessel disease in 130 patients - 25%. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0
2

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
2
1
0
2
Order By: Relevance
“…Multivessel involvement in patients with STEMI is not an uncommon finding; 50% MVD in our study is aligned with the reported frequency of as high as 44% to 66% in patients with STEMI [10][11][12]14,15]. MVD has been proven to be a significant prognostic marker with significantly higher rates of associated morbidities and mortalities [10][11][12]. Multivessel involvement is found to be associated with various clinical and demographic factors such that patients with MVD are older in age as compared to patients with SVD, comorbid conditions such as HTN and DM are more common, and patients with MVD have more complex and severe diseases with a higher proportion of type C lesions and a higher thrombus grade [10,12,14,16,17].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Multivessel involvement in patients with STEMI is not an uncommon finding; 50% MVD in our study is aligned with the reported frequency of as high as 44% to 66% in patients with STEMI [10][11][12]14,15]. MVD has been proven to be a significant prognostic marker with significantly higher rates of associated morbidities and mortalities [10][11][12]. Multivessel involvement is found to be associated with various clinical and demographic factors such that patients with MVD are older in age as compared to patients with SVD, comorbid conditions such as HTN and DM are more common, and patients with MVD have more complex and severe diseases with a higher proportion of type C lesions and a higher thrombus grade [10,12,14,16,17].…”
Section: Discussionsupporting
confidence: 90%
“…Multivessel involvement in patients with STEMI is not an uncommon finding; 50% MVD in our study is aligned with the reported frequency of as high as 44% to 66% in patients with STEMI [10][11][12]14,15]. MVD has been proven to be a significant prognostic marker with significantly higher rates of associated morbidities and mortalities [10][11][12].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…В контраст с широкодостъпната и добре разработена интервенционална мрежа с установени практики за първична ПКИ, проследяването на нашите като цяло високорискови пациенти впоследствие е неясно. Дългосрочният ефект от предприетите интервенционални терапевтични стратегии също остава с въпросителна [45][46][47]. У нас поетапната планова реваскуларизация безспорно е част от рутинната практика, особено в големите центрове и в нискорисковите популации пациенти.…”
unclassified
“…У нас поетапната планова реваскуларизация безспорно е част от рутинната практика, особено в големите центрове и в нискорисковите популации пациенти. Проследените и публикувани резултати за тази актуална за нас популация, включваща вероятно по-широк рис ков спектър пациенти в сравнение с рандомизираните проучвания в световен мащаб, са все още епизодични и оскъдни [47][48][49]. Установяването на тенденциите, успехите и пропуските в локалната клинична практика е съществена стъпка в изготвянето на прицелни здравни политики, както и в насочване на усилията на специалистите към ефективни терапевтични подходи при проследяването на пациентите с преживян SТЕМI.…”
unclassified